Effects of dietary cinnamon bark on quality, texture profile, and other physicochemical features of broiler carcase - Mohammed M. Qaid; Saud I. Al-Mufarrej; Maged A. Al-Garadi; Abdulaziz A. Al-Abdullatif; Gamaleldin M. Suliman; Abdulmohsen H. Alqhtani; Rashed A. Alhotan; Abdulrahman S. Alharthi; Mutee A. Murshed (Italian Journal of Animal Science)
The bark of Cinnamomum verum (CVB) had beneficial effects on the meat quality of broilers associated with phytochemical products, such as cinnamaldehyde. This study aimed to assess the potential effects of supplementation with CVB on the breast quality and carcase features of broilers. A total of 120 broiler chicks were arbitrarily assigned to four dietary treatment groups, each with five replicates (♂:♀ = 3:3 in each replicate). Each experimental meal was designed to contain a basal diet with 0, 2, 4, and 6 g CVB/kg. On day 34, 1 male broiler from each replication was selected for selected criteria. The present findings revealed that the broilers treated with CVB, especially at 2 g CVB, increased (p < 0.05) meat quality compared to control through improved water holding capacity (WHCM), lowered shrinkage rate during cooking, and lower shear force (SF) as an indicator of tenderness. CVB-treated groups lowered springiness and reduced relative abdominal fat weight. The 6 g CVB reduced the cohesiveness, initial values of yellowness, browning index, and saturation index, as well as the final values of lightness, hue angle, and whiteness index. The relative weights of leg, liver, and small intestine were higher (p < 0.05) in the broilers treated with 4 g CVB compared to other groups. In conclusion, the use of CVB as a natural preservative, especially at 2 g, can extend the shelf life and improve the quality of broiler breast fillets.